TOWARD AN ECOCENTRIC CHRISTIAN ECOLOGY: An Interreligious Case Study in Indigenous and Christian Eco‐Activism. Issue 4 (1st February 2022) - Waters, James W.
ABSTRACT: Anthropocentrism is an old and persisting problem for Christian ecology. This article argues that one way Christian ecological ethics can begin moving beyond anthropocentrism is by looking outside itself to other traditions that practice and observe a more ecocentric ethic. Specifically, it suggests an engagement with indigenous traditions of North America. Holding up the ecocentric tactics and discursive strategies employed by the Standing Rock Sioux Tribe (SRST) during the 2016 Dakota Access Pipeline (DAPL) protests the article shows how American Indian ecologies can help move Christians toward a more ecocentric worldview. It then examines the ways certain Christian groups approached their allyship with the SRST during the DAPL protests and asks which of these groups approached this case of interreligious, ecological resistance most effectively as allies. That is, it asks which Christian groups partnered with the SRST in ways that actually aided the protests and, additionally, fostered the possibility of learning from the SRST's ecocentric, indigenous religious ecology. The aim is to provide an example of how collaborative, respectful, anticolonial dialogue and allyship can happen between Christian and indigenous eco‐activists in a way that is mutually beneficial.